2022
DOI: 10.1007/s12274-022-4822-4
|View full text |Cite
|
Sign up to set email alerts
|

Zero-oxidation state precursor assisted fabrication of highly dispersed and stable Pt catalyst for chemoselective hydrogenation of α,β-unsaturated aldehydes

Abstract: The chemoselective hydrogenation of α, β-unsaturated aldehydes is a key strategy for the synthesis of fine chemicals. Herein, we developed an efficient method of depositing Pt particles on FeOx/SBA-15. This strategy is dependent on using a platinum-divinyltetramethyldisiloxane complex (Pt 0 -DVTMS) as the precursor, which we demonstrate can be removed through a H2-treatment under mild conditions. This, in turn, allowed for the synthesis of catalysts with well dispersed Pt particles. The presence of FeOx specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Therefore, for Ni-based c lysts in the DRM process, it is crucial to solve the problem of carbon deposition to main the activity and stability simultaneously. Sintering is the migration and agglomeration of the active metal at high temperatures, which reduces the number of active sites, resulting in a decrease in the activity of the catalyst [26]. The oxidation of active metals during the reaction and its reaction with the support or promoters, as well as the collapse of the pore structure of the catalyst support at high temperatures, will also cause catalyst deactivation.…”
Section: Catalyst Deactivation Mechanismmentioning
confidence: 99%
“…Therefore, for Ni-based c lysts in the DRM process, it is crucial to solve the problem of carbon deposition to main the activity and stability simultaneously. Sintering is the migration and agglomeration of the active metal at high temperatures, which reduces the number of active sites, resulting in a decrease in the activity of the catalyst [26]. The oxidation of active metals during the reaction and its reaction with the support or promoters, as well as the collapse of the pore structure of the catalyst support at high temperatures, will also cause catalyst deactivation.…”
Section: Catalyst Deactivation Mechanismmentioning
confidence: 99%
“…The supported NiBi IMCscatalyst synthesized by Yu et al, [186] who has made a breakthrough in the preferential hydrogenation of various unsaturated aldehydes to C═O. Liang et al [187] reported Pt loading on FeO x /SBA-15 (Pt/FeO x /SBA-15), the presence of FeO x enhances the interaction between Pt and the carrier with the selectivity of 92% and yield of 89% for cinnamyl alcohol. In view of the difficulty of selective hydrogenation of 𝛽-unsaturated ketones to produce unsaturated alcohols 𝛼, Ouyang et al [188] reduced the particle size of the heteroge-neous catalyst from nanometers to clusters, propiophenone selective hydrogenation to unsaturated alcohols occurred on Au nanoclusters protected by precise sulfate of Au 25 (SR) 18 atoms, and showed selectivity of 100%.…”
Section: Selective Hydrogenation Of Unsaturated Aldehyde Ketonementioning
confidence: 99%
“…Liang et al. [ 187 ] reported Pt loading on FeO x /SBA‐15 (Pt/FeO x /SBA‐15), the presence of FeO x enhances the interaction between Pt and the carrier with the selectivity of 92% and yield of 89% for cinnamyl alcohol. In view of the difficulty of selective hydrogenation of β‐unsaturated ketones to produce unsaturated alcohols α, Ouyang et al.…”
Section: Research Progress Of Sacs In Petrochemical Catalytic Reactionmentioning
confidence: 99%
“…Generally, two parameters, catalytic performances (conversion and selectivity) and costs of catalysts, are mainly considered for the desirable catalysts. 9 The precious metal-based catalysts, such as Pt, Au, Ag, Ir, Ru, Rh, Os and Pd, have been widely explored toward CTH reaction of α, β-unsaturated aldehydes 4,[17][18][19] . However, their high costs and somewhat unsatisfactory selectivity limit their wide applications.…”
Section: Introductionmentioning
confidence: 99%